Malaysian Young Consumers’ Purchase Intention Through Social Media Platform During Global Pandemic - Yeow JianAi; Cheah Chew Sze; Yeo Sook Fern; Cheang Yu Wan (International Journal of Entrepreneurship, Business, and Creative Economy, 2022)
Many accidents happened in the year 2020, such as bushfires, crashes, and the deathly pandemic of Covid 19. The year 2020 was undoubtedly going down in history as one of the worst years ever. Till now, in the year 2021, many countries are still under restriction control, and some countries are imposing a total lockdown. In June 2021, Malaysia was facing the third wave of the Covid-19 pandemic triggering a nationwide lockdown and limiting interstate travel. In July 2021, Malaysia's daily Covid-19 cases had exceeded more than 10,000 and brought up a total of 1 million cases, with a population of approximately 32-33 million. Many businesses were affected badly during the pandemic. Some big corporations were forced to shut down their productions, causing huge numbers of unemployment in the country due to layoff and contract termination. Some businesses have started to implement electronic business (e-business) and utilize social media platforms such as Facebook and Instagram for advertisements to attract more buyers, especially young consumers. The purchasing power of youth consumers is relatively high in Malaysia, and this study aims to identify the causes of young consumer purchase intention using social media during the global pandemic. This study helps the local businesses to sustain their business adapt to the new norms. There are five main variables being tested in this study, and the variables were being validated using. The independent variables included in this study are perceived ease of use, perceived usefulness, performance expectancy, interactivity, and intention to express empathy. Quantitative data analysis was done and concluded that perceived ease of use, perceived usefulness, and interactivity have a significant relationship with young consumer purchase intention using social media. Interestingly, performance expectancy and intention to express empathy have no significant relationship with young consumer purchase intention during the pandemic. This study helps to create awareness for the local businesses to focus on more interactive types of marketing, making the social media platform easy to use and providing more useful information to their customers.